2015
DOI: 10.1016/j.parkreldis.2015.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Elevated salivary protein in Parkinson's disease and salivary DJ-1 as a potential marker of disease severity

Abstract: Introduction: There is an urgent need to identify robust biomarkers for Parkinson's disease (PD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 12 publications
1
41
0
Order By: Relevance
“…When the miRNA expression profile in NPC and furthermore in other malignancies has been fully understood, early diagnosis and even screening of the disease may become a reality. These earlier studies beginning in 2004 and recent studies help pave a way to saliva being a useful diagnostic medium for a variety of contexts: Systemic diseases : many studies have been published to link salivary transcriptomic profiles to diseases affecting large populations: acute myocardial infarction (12–15), diabetes mellitus (16), Sjogren’s syndrome (17), developmental issues concerning premature neonates (18), cystic fibrosis (19, 20), and Parkinson’s disease (2123). Based on a pilot study, matrix metalloproteinases may show elevated levels in saliva among patients with oral vesiculoerosive diseases acting as potential diagnostic markers or therapeutic targets (24).…”
Section: Salivary Biomarkersmentioning
confidence: 99%
“…When the miRNA expression profile in NPC and furthermore in other malignancies has been fully understood, early diagnosis and even screening of the disease may become a reality. These earlier studies beginning in 2004 and recent studies help pave a way to saliva being a useful diagnostic medium for a variety of contexts: Systemic diseases : many studies have been published to link salivary transcriptomic profiles to diseases affecting large populations: acute myocardial infarction (12–15), diabetes mellitus (16), Sjogren’s syndrome (17), developmental issues concerning premature neonates (18), cystic fibrosis (19, 20), and Parkinson’s disease (2123). Based on a pilot study, matrix metalloproteinases may show elevated levels in saliva among patients with oral vesiculoerosive diseases acting as potential diagnostic markers or therapeutic targets (24).…”
Section: Salivary Biomarkersmentioning
confidence: 99%
“…DJ-1 has also been assessed in saliva. Once saliva composition and total protein content had been accounted, there were similar levels in 16 PD cases and 22 controls in one study and 74 PD cases with 12 controls in a further study, with inconsistent correlation using various clinical scores of severity [99,100].…”
Section: Dj-1mentioning
confidence: 91%
“…There has been recent interest in saliva as a fluid for biomarker discovery in Parkinson's disease (PD). Several studies, which focused on various aspects of saliva composition, have reported data on salivary protein concentration in patients with PD …”
mentioning
confidence: 99%
“…Several studies, which focused on various aspects of saliva composition, have reported data on salivary protein concentration in patients with PD. [1][2][3] We conducted a systematic review and meta-analysis to combine data on protein concentration across these studies and assess the magnitude of difference between patients and controls. PubMed and EMBASE were searched for the terms "Parkinson's disease" and "saliva."…”
mentioning
confidence: 99%
See 1 more Smart Citation